2014
DOI: 10.1002/ajp.22274
|View full text |Cite
|
Sign up to set email alerts
|

The genetic population structure of wild western lowland gorillas (Gorilla gorilla gorilla) living in continuous rain forest

Abstract: To understand the evolutionary histories and conservation potential of wild animal species it is useful to assess whether taxa are genetically structured into different populations and identify the underlying factors responsible for any clustering. Landscape features such as rivers may influence genetic population structure, and analysis of structure by sex can further reveal effects of sex-specific dispersal. Using microsatellite genotypes obtained from noninvasively collected fecal samples we investigated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 74 publications
3
36
1
Order By: Relevance
“…Alternatively, it is possible that following its introduction, SIVgor may have not yet spread beyond southern Cameroon. The home ranges of gorilla groups are small compared with chimpanzees, and their movements, as inferred from gene flow, are influenced by both major and smaller rivers, perhaps more so than the migration of chimpanzees (28)(29)(30). It has been estimated that SIVgor sequence distances reflect at least 100-200 y of diversification (15).…”
Section: Sivgor In Gorillas Is Less Common and Widespread Than Sivcpz Inmentioning
confidence: 99%
“…Alternatively, it is possible that following its introduction, SIVgor may have not yet spread beyond southern Cameroon. The home ranges of gorilla groups are small compared with chimpanzees, and their movements, as inferred from gene flow, are influenced by both major and smaller rivers, perhaps more so than the migration of chimpanzees (28)(29)(30). It has been estimated that SIVgor sequence distances reflect at least 100-200 y of diversification (15).…”
Section: Sivgor In Gorillas Is Less Common and Widespread Than Sivcpz Inmentioning
confidence: 99%
“…Autosomal analysis has typically focused on analysis of short tandem repeats (STRs) (e.g., Becquet et al 2007;Nater et al 2013;Fünfstück et al 2014), with increasing numbers of whole-genome sequences recently becoming available (Prado-Martinez et al 2013;Xue et al 2015) and providing a rich picture of population structure and demographic history. Maternally inherited mitochondrial DNA (mtDNA) has also been widely exploited, progressing from sequencing of the hypervariable regions (Fischer et al 2006) to the maximum possible resolution of the whole molecule (Hvilsom et al 2014).…”
mentioning
confidence: 99%
“…Field researchers thus correctly identified chimpanzee dung in 227/242 = 94% of cases. In a reciprocal analysis of genotypes purportedly from gorillas and typed as part of a complementary study (Fünfstück et al, 2014), we found 16 samples were derived from chimpanzees. These 16 samples were secondarily genotyped at microsatellite loci used here.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we compared the genetic differentiation between groups drawn from the same subspecies and between groups drawn from different subspecies. Such use of various methods is highly recommended for attempting to obtain an unbiased, accurate and comprehensive view about the genetic structure of the populations under study (Frantz et al, 2009; Schwartz and McKelvey, 2009; Fünfstück et al, 2014). …”
Section: Discussionmentioning
confidence: 99%